Fodder Preparation Practices Adopted by Community Subsistence Farmers in Zimbabwe in the Face of Climate Change: A Case Study of the Garanyemba Community Ward 13 in the Gwanda District, Matabeleland South Province. - Kumalo, Judith; Manyani, Albert (European Journal of Applied Sciences, 2023)
The study identifies methods and practices adopted by communal subsistence farmers in preparing fodder for their livestock in the face of climate change. The purpose is to enhance fodder availability in the Garanyemba Ward 13, Gwanda District in Matabeleland South Province, Zimbabwe. Explored are challenges that affect methods / practices of fodder preparation on which livestock depends; without which communities cannot survive. The study employed a mixed methods research methodology; gathering data through face-to-face in-depth semi-structured interviews and questionnaire. Analysis was through descriptive statistics, thematic and content analysis methods. Findings suggest that Garanyemba communal farmers are overwhelmed with numerous problems that affect fodder availability. Mountains and inselbergs have deprived the Ward of its agricultural land and crop residues; a critical component of fodder. Climate change has caused droughts, low rainfall, water shortage, non-availability of grass and premature drying of rivers and wetlands which are the main sources of water. This has caused serious shortage of fodder; and affected livestock productivity. These challenges have driven communities to prepare fodder to protect livestock against feed shortage; and losses during dry seasons. Cutting grass, crop residues, the ‘cut and carry’ system, ‘emilageni’ – the ‘lagisa’ system; and novel initiatives comprise the main methods of fodder preparation. Water harvested through sand dams helps to grow fodder. Training has improved communities’ skills to make fodder. Recommendations include construction of micro–dams, more sand dams and piping water from the Thuli River to avail water; and start irrigation schemes to grow fodder. Workshops and refresher courses on fodder preparation are encouraged to skill communal subsistence farmers.